Tailoring cation vacancies in Co, Ni phosphides for efficient overall water splitting. (5th December 2022) - Sun, Shuai; Wang, Tianci; Qian, Kejiang; Zhang, Hao; Ji, Kaifeng; Shi, Zijian; Chen, Mingyu; Zhang, Cui; Liu, Shuangxi
Abstract: High-efficiency water splitting catalysts are competitive in energy conversion and clean energy production. Herein, a bifunctional water splitting catalyst CoNiP with cation vacancy defects (CoNiP–V) is constructed through defect engineering. The results show that abundant cation vacancy defects in CoNiP–V are bifunctional active centers in the process of water electrolysis, which enhance the activity of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). In 1.0 mol L −1 potassium hydroxide, CoNiP–V requires a pretty low overpotential of 58 mV to reach a geometrical current density of 10 mA cm −2 for HER. To deliver a current density of 100 mA cm −2, only 137 mV and 340 mV of overpotential are needed for HER and OER, respectively. Moreover, the cell with CoNiP–V as both cathode and anode exhibits good stability, which only needs 1.61 V to achieve a current density of 100 mA cm −2, and the cell voltage barely rises 10% after 100 h' test under 100 mA cm −2 . Therefore, CoNiP–V is promising for the development of efficient water splitting catalysts. Graphical abstract: Cation vacancy defects are recognized as the bifunctional active sites of CoNiP–V, which promote discharge of H2 O and OH − and thus accelerating the generation of H2 and O2 . The bifunctional CoNiP–V exhibits exceptional overall water splitting performance, which is promising in energy conversion and clean energy production. Image 1 Highlights: Bifunctional CoNiP catalyst with cation vacancy defects (CoNiP–V) was prepared. Cation vacancy defects are recognized as the bifunctional active sites of CoNiP–V. Cation vacancy defects promote discharge of H2 O and OH −, thus accelerating production of H2 and O2 . The bifunctional CoNiP–V exhibits exceptional overall water splitting performance.